A Rare Manifestation of Cervical Yolk Sac Tumor in an Unfortunate Infant - Jeyasakthy Saniasiaya; Suzina Sheikh Ab Hamid; Hazama Mohamad; Wan Nur Najmiyah Wan Abdul Wahab; Norzaliana Zawawi (Turkish Archives of Otorhinolaryngology, 2019)

(untitled)
Paediatric germ cell tumor is composed of various neoplasms which exhibit capricious clinical presentation and histological features depending on the age and the area of presentation. Yolk sac tumor is an extremely rare malignant tumor of embryonic origin which usually arises from the gonads. Its manifestation in the head and neck region is extremely rare. Here, we report a rare case of the malignant transformation of mature teratoma into yolk sac tumor of the neck in an infant. Diagnosis was confirmed following histopathological examination of the neck mass along with marked increase of the serum alpha-fetoprotein. The child unfortunately succumbed prior to chemotherapy. We highlight the challenge we faced in diagnosing and managing this rare entity. We would also like to recommend serial monitoring of serum alpha-fetoprotein in all patients with mature teratoma to detect malignant transformation early.